Dynamic behavior of suspending nanodroplets with coming nanodroplets on solid surfaces: A molecular dynamics study - Liwei Sun; Xiaochun Pan; Jiachao Gu; Baocheng Zhan (PLoS ONE, 2025)
The impingement of binary droplets upon solid surfaces has received growing attention in recent years because of its wide applications in industry. Although the dynamic evolution of impacting single droplets is relatively well satisfied, the understanding of impacting binary droplets remains inadequate, especially at the nanoscale. This paper uses molecular dynamics (MD) simulations to investigate the impact behavior of suspending nanodroplets with coming nanoscale ones to address this gap. The wettability of solid surfaces and the impact We are selected in a wide range to obtain an overall insight into the impingement of targeted systems. Firstly, the representative dynamics are recognized from snapshots to observe the corresponding instantaneous evolution at the molecular level. Secondly, the maximum spreading of impacting binary droplets during coalescence (primary spreading) and extension upon solid surfaces (secondary spreading) is investigated. Finally, the contact time of targeted systems is discussed by extracting data from numerical simulations over a wide range of We and intrinsic contact angles. The present work can provide a guideline for the application of impacting multiple nanodroplets, which requires a controllable spreading diameter or quick detachment of impacting nanodroplets.